PENGARUH LEVERAGE, TAX HAVEN, DAN KEPEMILIKAN MANAJERIAL TERHADAP AGRESIVITAS PAJAK DENGAN KOMISARIS INDEPENDEN SEBAGAI VARIABEL MODERASI - Chyntialie; Ngadiman; Yustina Peniyanti Jap (Fakultas Ekonomi Universitas Tarumanagara, 2025)
The purpose of this research is to determine the effect of Leverage, Tax Haven and Managerial Ownership on Tax Aggressiveness with Independent Commissioner as Moderating Variable. This study uses secondary data taken from the official IDX website. This study used 105 samples, namely manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) during the period 2016 – 2020. The results of this study indicate that Leverage, Tax Haven and Managerial Ownership have a positive effect on Tax Aggressiveness with Independent Commissioners as Variables Moderation.